CONTRACTS AS AN ELEMENT OF QUALITY ASSURANCE OF IT PRODUCTS - Pogorielovska, I. D.; Horbovyy, A. Yu.; Hladchenko, O. V.; Ratushnyak, T. V. (Systems and Technologies, 2025)
The importance of high-quality IT products in the modern digital world is considered; the SQuaRE series of interna- tional standards is analyzed, which defines requirements for the quality of systems and software, for quality measurement and recommendations for evaluating a software product; it is emphasized that ensuring the quality of IT products is not only about quality models, guidelines for evaluating functionality, checking code or testing a product, but also about ensuring high quality of execution of all stages of the product life cycle, starting from the formation of customer requirements and until obtaining the final result; an analysis of studies devoted to the application of contract models in software engineering is performed; the fea- tures of contracts in the IT sector, which are custom or highly specialized, due to the specifics of the subject of the contract, are indicated; the content of the contract, which provides it with the role of a quality control mechanism for IT products, is defined, namely: requirements, quality standards, scope of work and the procedure for calculating its cost, deadlines, criteria for accept- ing results, key performance indicators, formal verification procedures that provide the opportunity to control quality at each stage, change management rules and the responsibility of the parties for breach of obligations, as well as the speed of product development, roles in the team, defect accounting system, backlog clarification sessions, methods for assessing the complexity of task performance; the content characteristics and differences between the Fixed Price, Time&Materials, Dedicated Team contract models and their impact on ensuring the quality of IT project implementation are investigated; conclusions are drawn that when choosing the type of contract model, it is necessary to take into account the specifics of the IT project and the available budget, the number of uncertainties in the project and the willingness to take risk; prospects for further research are outlined – the potential of Smart contracts, which are currently being integrated into various areas of the IT industry.